Impact of Celebrity Endorsements on Brand Image - Mukherjee, Debiprasad (Indian Journal of Marketing, 2012)
Celebrity endorsements have been established as one of the most popular tools of advertising in recent times. It has become a trend and is perceived as a winning formula for product marketing and brand building. It is easy to choose a celebrity, but it is tough to establish a strong association between the product and the endorser. While the magnitude of the impact of celebrity endorsement on brands remains under the purview of gray spectacles, this paper is an effort to analyze the impact of celebrity endorsements on brands. The objective of this paper is to examine the relationship between celebrity endorsements and brands, and eventually, its impact on consumer's buying behavior as well as their brand preferences. The paper also proposes a 20 point model which can be used as a blue-print criterion and can be used by brand managers for selecting celebrities and capitalizing the celebrity resource through 360 degree brand communication, which is regarded as the foundation of the impact of celebrity endorsements. Purpose: To study the impact of the celebrity endorsement on effective brand management and evaluate associated factors that contribute to the success or failure of the endorsement. Approach: This work was done mainly as an exploratory research to find out the correlation between celebrity endorsement and brand image based on the structured questionnaire, and analysis is done on the response with the help of higher order statistical tools. Findings: Three categories of research findings have been deduced from the study. The first category dealing with the customer’s perception about celebrity endorsements. The second aspect is the factors those should be taken into account while endorsing a celebrity. And the last aspect is the formulation of a strategic model that can be used while doing a celebrity endorsement. Value: This particular work will have a significant impact on the study of celebrity endorsement impact on brand building process and can be used for further research work on the same area.